2020
DOI: 10.4314/sajas.v50i4.11
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizae inoculation of einkorn wheat affects fatty acid, nutrient and mineral concentrations

Abstract: The purpose of this study was to determine the effect of arbuscular mycorrhizae (AM) inoculation, which was administered to increase the quality of einkorn wheat in its fatty acid composition, quality and mineral concentration. Wheat grown from AM inoculated seed (AM+) had increased the dry matter (DM), iron (Fe), monounsaturated fatty acids (MUFA), especially oleic acid, and alpha-linolenic acid, and cis-5,-8,-11,-14, and cis-17 eicosapentaenoic acid from polyunsaturated fatty acids (PUFA) (P <0.05), but d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Moreover, the percentage of MUFA found in our study for common and durum wheat was in the same range as in the study mentioned above, where it was found at 16-24% [52]. The MUFA percentage of einkorn was in accordance with a study of a Turkish cultivar, reporting it at 32% [53]. The statistically higher percentage of MUFA in einkorn and emmer, compared to common wheat, was also reported by Suchowilska et al, 2009 [54], who found that einkorn had significantly higher MUFA % than emmer, which was not observed in our dataset.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the percentage of MUFA found in our study for common and durum wheat was in the same range as in the study mentioned above, where it was found at 16-24% [52]. The MUFA percentage of einkorn was in accordance with a study of a Turkish cultivar, reporting it at 32% [53]. The statistically higher percentage of MUFA in einkorn and emmer, compared to common wheat, was also reported by Suchowilska et al, 2009 [54], who found that einkorn had significantly higher MUFA % than emmer, which was not observed in our dataset.…”
Section: Discussionsupporting
confidence: 91%
“…Table (2) showed significant effect of inoculation on protein percent% max value(28.207%) of Mung bean because increased Mycorrhzia on root and nodules which responsible on nitrogen fixation this accepted [5,13] ,also showed significant effect of Nano Zn fertilizers on protein percent of Mung bean, max value(27.387%) in treatment 3 g.l -1 because of increased Nano element passed through plasma membrane it is very small size and increased activity of enzymes which responsible on protein synthesis this accepted [5,14,21].also showed significant effect of interaction of Nano Zn and inoculation max value(30.823%) in inoculation and 3 g. l-1 because of roles of Nano Zn as stimulator to photosynthesis and nitrogenase enzymes this accepted with [4,7,15]. (3) showed significant effect of inoculation on carbohydrates percent% max value(49.078%) of Mung bean because increased precursor of photosynthesis enzymes and mycorrhzial and root nodules provided all types of amino acids depend on type of organic acids come from Krebs cycles this accepted with [5,16] ,also showed significant effect of Nano Zn fertilizers on carbohydrates percent of Mung bean max value(47.84%) in treatment 3 g.l -1 because of increased Nano element passed through plasma membrane it is very small size and increased activity of enzymes which responsible on carbohydrates synthesis this accepted with [5,14].also showed significant effect of interaction of Nano Zn and inoculation max value(53.62%) in inoculation and 3 g. -1 because of roles of Nano Zn as stimulator to photosynthesis and nitrogenase enzymes this accepted with [4,7,15]. 4) showed significant effect of inoculation on Fats percent% max value (2%) of Mung bean because increased precursor of Fats synthesis enzymes in mycorrhzial and root nodules provided all types of amino acids depend on type of organic acids come from Krebs cycle this accepted with [5] [16] ,also showed significant effect of Nano Zn fertilizers on Fats percent of Mung bean, max value(1.97%) in treatment 3 g.l -1 because of increased Nano element passed through plasma membrane it is very small size and increased activity of enzymes which responsible on Fats synthesis this accepted with [5,14].also showed significant effect of interaction of Nano Zn and inoculation max value(2.0937%) in inoculation and 3 g. -1 because of roles of Nano Zn as stimulator to Fats synthesis and nitrogenase enzymes this accepted with [4,7,…”
Section: Protein Percent %mentioning
confidence: 91%
“…(3) showed significant effect of inoculation on carbohydrates percent% max value(49.078%) of Mung bean because increased precursor of photosynthesis enzymes and mycorrhzial and root nodules provided all types of amino acids depend on type of organic acids come from Krebs cycles this accepted with [5,16] ,also showed significant effect of Nano Zn fertilizers on carbohydrates percent of Mung bean max value(47.84%) in treatment 3 g.l -1 because of increased Nano element passed through plasma membrane it is very small size and increased activity of enzymes which responsible on carbohydrates synthesis this accepted with [5,14].also showed significant effect of interaction of Nano Zn and inoculation max value(53.62%) in inoculation and 3 g. -1 because of roles of Nano Zn as stimulator to photosynthesis and nitrogenase enzymes this accepted with [4,7,15]. 4) showed significant effect of inoculation on Fats percent% max value (2%) of Mung bean because increased precursor of Fats synthesis enzymes in mycorrhzial and root nodules provided all types of amino acids depend on type of organic acids come from Krebs cycle this accepted with [5] [16] ,also showed significant effect of Nano Zn fertilizers on Fats percent of Mung bean, max value(1.97%) in treatment 3 g.l -1 because of increased Nano element passed through plasma membrane it is very small size and increased activity of enzymes which responsible on Fats synthesis this accepted with [5,14].also showed significant effect of interaction of Nano Zn and inoculation max value(2.0937%) in inoculation and 3 g. -1 because of roles of Nano Zn as stimulator to Fats synthesis and nitrogenase enzymes this accepted with [4,7,15].…”
Section: Protein Percent %mentioning
confidence: 96%
See 1 more Smart Citation
“…The cited authors indicated a higher gizzard weight, which corresponds to the results of the research by Gabriel et al (2008) , in which the effect of using wheat grain on the development of the digestive system of broiler chickens was assessed. Wheat is a widely used grain in poultry nutrition due to its easy availability and metabolic energy content ( Pirgozliev et al, 2003 ; Ayasan et al , 2020 ). In the last stage of chicken nutrition, the feed has a reduced protein level and an increased level of metabolic energy.…”
Section: Introductionmentioning
confidence: 99%